PENGARUH PERBAIKAN BERKESINAMBUNGAN TERHADAP KINERJA KARYAWAN (STUDI KASUS DI PT.RENTANG BUANA NIAGAMAKMUR TASIKMALAYA) - Sri Sudiarti (Jurnal Maps (Manajemen Perbankan Syariah), 2019)
The objectives of this research are to know and to analyze about the effect of Continuous Improvement on the performance of employees at PT. Rentang Buana Niagamakmur (PT.RBN) Tasikmalaya. Research method which applied in this research is survey research method, while data collecting technique is done by through questionaire. Sampling technique applies sample is accidental sampling technique and the size sample is 55 respondents. Data analysis techniques used in the study is simple regression technique, analysis of the coefficient of determination  and t test. The results showed that the Continuous Improvement  including both criteria, including employee performance criteria, as well as Continuous Improvement  has a positive influence on employee performance of 76,4% in PT . Rentang Buana Niagamakmur (PT.RBN) Tasikmalaya.